Emotional Maltreatment and Adolescent Depression: Mediating Mechanisms and Demographic Considerations in a Child Welfare Sample. Issue 5 (31st March 2020) - McNeil, Shiesha L.; Andrews, Arthur R.; Cohen, Joseph R.
Abstract : Emotional maltreatment is a risk factor for adolescent depression. Yet, it remains unclear whether commissions and omissions of emotional maltreatment (a) confer vulnerability via distinct mechanisms and (b) demonstrate similar risk across adolescent subpopulations. The present, multiwave study examined whether school engagement and peer relationships explain the depressive effects of distinct emotional maltreatment subtypes in an at‐risk child welfare sample ( N = 657; ages 11–14, AgeMean = 12.49). The findings indicated that commission subtypes of emotional maltreatment predicted increasing depressive symptoms via increasing peer relationship problems, especially for girls. Meanwhile, decreasing school engagement was a depressogenic risk pathway for Hispanic adolescents reporting omission subtypes of emotional maltreatment. The results emphasize the importance of distinguish between emotional maltreatment subtypes to identify specific risk pathways for adolescent depression.